Proximity Effect in Crystalline Framework Materials: Stacking‐Induced Functionality in MOFs and COFs - Kuc, Agnieszka; Springer, Maximilian A.; Batra, Kamal; Juarez‐Mosqueda, Rosalba; Wöll, Christof; Heine, Thomas (Advanced functional materials, 2020)
Metal–organic frameworks (MOFs) and covalent organic frameworks (COFs) consist of molecular building blocks being stitched together by strong bonds. They are well known for their porosity, large surface area, and related properties. The electronic properties of most MOFs and COFs are the superposition of those of their constituting building blocks. If crystalline, however, solid‐state phenomena can be observed, such as electrical conductivity, substantial dispersion of electronic bands, broadened absorption bands, formation of excimer states, mobile charge carriers, and indirect band gaps. These effects emerge often by the proximity effect caused by van der Waals interactions between stacked aromatic building blocks. Herein, it is shown how functionality is imposed by this proximity effect, that is, by stacking aromatic molecules in such a way that extraordinary properties emerge in MOFs and COFs. After discussing the proximity effect in graphene‐related materials, its importance for layered COFs and MOFs is shown. For MOFs with well‐defined structure, the stacks of aromatic building blocks can be controlled via varying MOF topology, lattice constant, and by attaching steric control units. Finally, an overview of theoretical methods to predict and analyze these effects is given, before the layer‐by‐layer growth technique for well‐ordered surface‐mounted MOFs is summarized. Crystalline framework materials offer an additional means for functionality design: controlled van der Waals stacks of aromatic building blocks are subject to the proximity effect and yield phenomena such as wide absorption bands, mobile charge carriers, or indirect band gaps. Such stacks are present in layered MOFs and COFs, and can be created via steric control in 3D frameworks.